Utilization of Main and Functional Facilities in UPTD Fishery Port Region II Air Bangis, West Sumatra - Nasution, Windi Mardini; Nasution, Polaris; Zain, Jonny (Jurnal Perikanan dan Kelautan, 2025)
The Air Bangis fish landing base is the only fish landing base in Sungai Beremas District, Pasan Barat Regency, and is classified as a type D fishing port. The imbalance between dense fishing activities and limited available facilities results in suboptimal fishing activities. This research was conducted using a survey method in May-June 2024 at the UPTD Regional II Air Bangis Fishing Port, West Sumatra Province. Data analysis used facility needs analysis and facility utilization level analysis. The facilities available at the Air Bangis Fish Landing Base consist of basic, functional, and supporting facilities. Of the 17 existing facilities, four whose utilization levels were analyzed were facilities that significantly influenced capture fisheries activities and were considered suboptimal in supporting dense fishing activities, namely land, docks, depth and area of ​​port ponds, and TPI. The level of facility utilization obtained a value ranging from 17 to 61%, consisting of 2 facilities that have a level of utilization exceeding the capacity of the available facilities so that they are included in the category of not optimal, namely the dock and harbor pool. In contrast, the TPI's utilization level does not exceed the available capacity; facilities that are not used are the ice factory, cold storage, and fuel tanks